NAA50 Is an enzymatically active Nα-acetyltransferase that is crucial for development and regulation of stress responses - Armbruster, Laura; Linster, Eric; Boyer, Jean-Baptiste; Brünje, Annika; Eirich, Jürgen; Stephan, Iwona; Bienvenut, Willy V.; Weidenhausen, Jonas; Meinnel, Thierry; Hell, Rüdiger; Sinning, Irmgard; Finkemeier, Iris; et al. (Plant physiology, 2020)
Nα-terminal acetylation (NTA) is a prevalent protein modification in eukaryotes. In plants, the biological function of NTA remains enigmatic. The dominant N-acetyltransferase (Nat) in Arabidopsis (Arabidopsis thaliana) is NatA, which cotranslationally catalyzes acetylation of ∼40% of the proteome. The core NatA complex consists of the catalytic subunit NAA10 and the ribosome-anchoring subunit NAA15. In human (Homo sapiens), fruit fly (Drosophila melanogaster), and yeast (Saccharomyces cerevisiae), this core NatA complex interacts with NAA50 to form the NatE complex. While in metazoa, NAA50 has N-acetyltransferase activity, yeast NAA50 is catalytically inactive and positions NatA at the ribosome tunnel exit. Here, we report the identification and characterization of Arabidopsis NAA50 (AT5G11340). Consistent with its putative function as a cotranslationally acting Nat, AtNAA50-EYFP localized to the cytosol and the endoplasmic reticulum but also to the nuclei. We demonstrate that purified AtNAA50 displays Nα-terminal acetyltransferase and lysine-ε-autoacetyltransferase activity in vitro. Global N-acetylome profiling of Escherichia coli cells expressing AtNAA50 revealed conservation of NatE substrate specificity between plants and humans. Unlike the embryo-lethal phenotype caused by the absence of AtNAA10 and AtNAA15, loss of NAA50 expression resulted in severe growth retardation and infertility in two Arabidopsis transfer DNA insertion lines (naa50-1 and naa50-2). The phenotype of naa50-2 was rescued by the expression of HsNAA50 or AtNAA50. In contrast, the inactive ScNAA50 failed to complement naa50-2. Remarkably, loss of NAA50 expression did not affect NTA of known NatA substrates and caused the accumulation of proteins involved in stress responses. Overall, our results emphasize a relevant role of AtNAA50 in plant defense and development, which is independent of the essential NatA activity.